POVERTY MITIGATION STRATEGIES OF THE RURAL WOMEN IN EJIGBO LOCAL GOVERNMENT AREA OF OSUN STATE, NIGERIA - IBITUNDE , I. O.; AJAYI, F. O.; OLAYODE , G. O.; AKINTAYO , A. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
Mitigating poverty has remained important among Nigeria’s developmental challenges. The study assessed the level of utilization of poverty mitigation strategies by the rural women in Ejigbo Local Government Area of Osun State, Nigeria. Specifically, it described the socio-economic characteristics of the rural women and examined the agricultural and non-agricultural poverty mitigation strategies utilized by the rural women in the study area. A multistage sampling procedure was used to select 120 rural women for the study. Primary data were collected with the aid of a well-structured interview schedule and analyzed with the use of frequency counts, percentages, mean, standard deviation and chi-square analysis. The results reveal that the mean age of the respondents was 42.1 years. The majority (73.3%) were married with a mean household size of 5 persons and the majority (60.8%) were members of a cooperative societ(ies). Personal savings (WMS= 2.78) ranked first among non-agricultural poverty mitigation strategies utilized by the respondents followed by petty trading (WMS = 2.64). Also, livestock keeping (WMS = 2.80) ranked first among the agricultural poverty mitigation strategies followed by selling farm produce (WMS = 2.44). A majority (65.0%) of the respondents were at a medium level of utilization of poverty mitigation strategies. Results of the hypothesis testing show that utilization of poverty mitigation strategies was significantly influenced by marital status (χ2=16.907, p≤ 0.05) and educational qualification (χ2=23.387, p≤ 0.01). The study recommended that favoured poverty mitigation strategies; personal savings, petty trading, livestock keeping and selling farm produce should be thoroughly examined to enable policymakers to know the right point of intervention.